PEMILIHAN SUPPLIER BAHAN BAKU PARTIKEL DENGAN METODE AHP DAN PROMETHEE - Wulandari, Ratri (Department Industrial Engineering, University of Muhammadiyah Malang, 2015)
The problem of choosing a supplier becomes very important to do a company to be able to meet consumer demand quickly and with quality. So far, the company has not implemented the supplier selection procedures and selection criteria not yet have a supplier. The method can be completed with the supplier selection criteria is the AHP method is used to determine the weights of criteria that have been corporations and PROMETHEE method used to determine the performance of the alternative. The purpose of this research is to identify the criteria used in the selection of a supplier company and determine the weight of these criteria and get ranked supplier to obtain the best supplier. The selected criteria in the selection of the supplier company is quality with a weight of 0.19, with a weight of 0.17 delivery, performance history with a weighting of 0.06, the price with a weighting of 0.36, communication system with a weighting of 0.06, the operating control with weights of 0.05, attitudes supplier with a weighting of 0.04 and a geographical location with a weight of 0.08 where as criteria rank order supplier is UD. TL as the first rank with a net value of flow for 0.254, UD. SD as the second rank with a value of 0.144 and a net flow PT.KTI as third with a net flow value of -0.397.